FRAMING MEDIA PROGRAM BADUNG ANGELUS BHUANA 2024 DAN PERSONAL BRANDING POLITIK GIRI PRASTA - Anastacia Patricia Novlina Nurak; Carolina Augi Widya Putri (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2026)
"This study analyzes how local media framed the Badung Angelus Bhuana (BAB) Program 2024 and how these framing patterns contributed to strengthening the political image of I Nyoman Giri Prasta ahead of the 2024 Regional Head Election (Pilkada) in Badung Regency, Bali. Specifically, the study employs Entman’s (1993) framing framework to identify problem definition, causal interpretation, moral evaluation, and treatment recommendation in coverage by local and regional online media from January 2023 to December 2024. The data were drawn from 26 news articles published by five local outlets (Bali Post, NusaBali, Radar Bali, Antara News, and Detik Bali) that explicitly contained the keywords “Badung Angelus Bhuana” or “BKK Badung.” The findings reveal one dominant pattern: the media consistently framed BAB as a positive policy closely associated with Giri Prasta, marked by a temporal shift from technocratic framing (budgetary information and procedures), to symbolic framing (emphasizing customary rituals and the narrative of “Badung sharing for Bali”), and ultimately to personalization framing (directly attributing the program’s success to Giri Prasta’s leadership). This pattern normalized BAB as a legitimate political instrument that is reasonable and worth continuing, while minimizing space for critique of governance aspects or the electoral calculations underlying the program. These findings underscore the importance of media framing analysis for understanding how public policy can be constructed as a source of political legitimacy within the context of decentralized democracy at the local level."